"Legitimate Violence" in the Prose of Counterinsurgency: An Impossible Necessity?. (May 2013) - Olsson, Christian
Drawing on a critical engagement with the claims made by (and interpretations of) the 2006 US army and marine corps field manual on "Counterinsurgency, " this article engages some of its underlying concerns with the problematic relation between violence, legitimacy, and political order. Since this manual draws heavily on many commonplaces of contemporary political science, the analysis explores their problematic presuppositions and the ways in which they play out in contemporary warfare. The primary conclusion is that while the encounter of legitimacy and violence is claimed by the doctrine to produce and maintain political order, its framing of this encounter is deeply rooted in a specific political order, that of the modern state, which severely constrains the conditions under which this encounter can take place. These constraints cast serious doubts on many of the doctrine's assertions, especially as they have shaped recent wars in Afghanistan and, until recently, in Iraq.